MERANCANG SISTEM PENGATURAN PROSES PRODUKSI KECAP MENGGUNAKAN METODE PROTOTYPE - Ferdyanto Taniwijaya; Syaiful Rahman; Abdul Munir S. (KHARISMA Tech, 2021)
PT. Adinata is one of the companies or factories engaged in food that makes and sells goods such as sweet soy sauce, chili sauce, vinegar, tauco, soy sauce, tomatoes. As for the background of this research is because the ordering of goods is still done manually so that it causes the production department to wait for sales to go home to find out customer orders, causing production to be long and not in order. In this study the authors made an Android-based ordering and production application system. The system itself consists of two parts. The first part is the web system and MySQL database which aims to produce from the list of orders that have been inputted by sales and will be processed by the production section, then the second part is the android application used by sales to input customer orders that will be forwarded to the production department. Testing of this study uses the System Usability Scale (SUS) developed by researchers and involved 20 respondents. After the evaluation is conducted, respondents are asked to answer the questions raised on the questionnaire and the results are used as a basis for drawing conclusions. The results of testing with the System Usability Scale (SUS) method resulted in an average score of 81 which shows that the system that was made received a very good rating from respondents.